Card Trick Exercise Leads to Improved Reading of Mathematics Texts. Issue 2 (7th February 2020) - Carducci, Olivia M.
Abstract: The activity described in this paper is based on the idea that reading an introductory undergraduate mathematics text is similar to reading instructions. I want my students to think about how to read when the goal is to learn to complete a task. I give them written instructions for doing a card trick and ask them to complete the trick. The subsequent discussion helps the students identify the reading strategies they used to complete the card trick; for example, reread the step to make sure you got it right. I point out the connections to reading their mathematics textbooks.